Finite Element Modeling of Slip Insert Geometric Grip Optimization for Oil Well Drill Pipes. (10th June 2020) - Tang, Liping; Guo, Baolin; Zhu, Xiaohua
Abstract : Drilling is being used to access ever-deeper oil and gas reservoirs, thereby presenting various challenges to the design and operation of down-hole tools. Slip inserts are suspension devices that are used to lower the drill pipe into the borehole and lift it to the wellhead, and their performance determines the extended depth of the borehole. In this paper, based on the field and laboratory test of the slip system, parameter sensitivity analysis is applied to the performance of a slip insert to guide the design of the latter. First, a mechanical model is developed of the drill pipe with the slip insert acting on it, and the stress acting on the drill pipe is analyzed theoretically by regarding the drill pipe as a thick-walled cylinder. Next, a numerical model is established to investigate how the slip-insert structure influences the drill-pipe stress, wherein the drill-pipe diameter is 5″ and the axial load is 180 tons . Finally, the results of a series of numerical simulations are presented. For the present slip insert and drill pipe, the optimum slip-insert parameter values are a front-rake angle of 70°, a back-rake angle of 30°, a tooth height of 2 mm, and zero chamfer.